Analysis and optimization of accuracy of measuring systems with disturbing sources of primary information - Блохін, Л. М.; Держак, С. В.; Петрова, Ю. В. (Proceedings of National Aviation University (archive), 2021)
The newest means and algorithms for analyzing the quality of the measuring system with disturbing sources of information are proposed.